8(x+2)+1=2x+6(3+x)

Simple and best practice solution for 8(x+2)+1=2x+6(3+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+2)+1=2x+6(3+x) equation:



8(x+2)+1=2x+6(3+x)
We move all terms to the left:
8(x+2)+1-(2x+6(3+x))=0
We add all the numbers together, and all the variables
8(x+2)-(2x+6(x+3))+1=0
We multiply parentheses
8x-(2x+6(x+3))+16+1=0
We calculate terms in parentheses: -(2x+6(x+3)), so:
2x+6(x+3)
We multiply parentheses
2x+6x+18
We add all the numbers together, and all the variables
8x+18
Back to the equation:
-(8x+18)
We add all the numbers together, and all the variables
8x-(8x+18)+17=0
We get rid of parentheses
8x-8x-18+17=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation

See similar equations:

| 251=33-v | | 2(4+x)-(3x-4)=8-2(x-2)+x | | 6x+4=5x+15 | | 9x-8+4=7x+8 | | -8=(x+11)/2 | | x/5+4=-5 | | 3/4y+1/3(y-4)=y+1/4 | | -10=-5x-5(-3x-8) | | 7=-10+3b+15 | | 5x+3+6x-1=35 | | 0,5x+6=10 | | (8x+12)/2=78 | | -7x+5=0 | | 233=-w+132 | | -4k+12=1 | | -32=3-7w | | 3/4(8x-4)-2/3)=-35 | | (6-t)+(7-t)-(4-t)=4 | | -10e+15=94-30e | | s^2+5^2-50=0 | | 1.2x-3.8x=1.6x+4.494 | | -96+7x=-4x+190 | | 3+4d−14=15−5d−4d3+4d-14=15-5d-4d | | (67+25)x=350+25x | | 8-2x5=-2 | | b/17-9b/17=40/17 | | 2f(5f-2)-10(f^2-3f+6)=-8f(f+4)+4(2f^2-f) | | 1/5y+8=-4/5y | | -u+170=73 | | 7+3+w=16 | | 10(3/2^x+1/5)=3/4 | | a/17=6 |

Equations solver categories